Compressive behavior of cylindrical rubber buffer confined with fiber reinforced polymer. Issue 3 (September 2020) - Pan, Shengshan; Zhao, Muzhou; Andrawes, Bassem; Zhao, Hang; Li, Lian
This paper presents a new composite buffer for mitigating the lateral displacement of structures under seismic loading. The buffer consists of a cylindrical rubber wrapped with fiber reinforced polymer composite. The uniaxial compressive stiffness of the buffer can be controlled by varying either the number of fiber reinforced polymer layers or the wrapping scheme of fiber reinforced polymer. First, a test program is carried out to investigate the impact of various parameters on the compressive stiffness and strength of the new buffer including thickness of fiber reinforced polymer, wrapping scheme, and method of wrapping of fiber reinforced polymer. Next, a theoretical formulation is derived to describe the constitutive behavior of fiber reinforced polymer wrapped rubber under uniaxial compression using strain energy density function of the Yeoh N-order polynomial model. Finally, a finite element model is developed to analyze the new composite buffer and the numerical results are validated using the experimental results. The results of the study show that the Yeoh model is able to simulate the behavior of rubber under compression. The new composite buffer exhibits significantly higher stiffness and strength than that of pure rubber. Wrapping scheme plays an important role in defining the mechanical behavior of the buffer. The study also shows good agreement between the numerical simulation and the experimental results.